2010
DOI: 10.1210/en.2009-1150
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a Indirectly Regulates Estrogen Receptor α Expression and Hormone Responsiveness in MCF-7 Breast Cancer Cells

Abstract: MicroRNA-27a (miR-27a) is expressed in MCF-7 breast cancer cells, and antisense miR-27a (as-miR-27a) induces ZBTB10, a specificity protein (Sp) repressor. Both as-miR-27a and overexpression of ZBTB10 decreased Sp1, Sp3, and Sp4 mRNA and protein expression in MCF-7 cells, and this was also accompanied by decreased levels of estrogen receptor alpha (ERalpha) mRNA and protein. RNA interference studies confirmed that basal expression of ERalpha was dependent on Sp1 but not Sp3 or Sp4 in MCF-7 cells. as-miR-27a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 42 publications
2
58
0
1
Order By: Relevance
“…It has also shown suggestive levels of association in hypothyroidism (32), atopic dermatitis (33) and self-reported allergy (34). ZBTB10 is thought to regulate specificity proteins Sp1, Sp3 and Sp4 (35,36); in cell culture studies, it is suppressed by ROSmicroRNA27a, thereby enhancing estrogen receptor α expression and mediating estrogen effects (36). Potential immunoregulation could either be through Sp1 (critical for interleukin [IL]-10 and CD40 responses) (37,38) or indirectly via estrogen effects on autoimmunity (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…It has also shown suggestive levels of association in hypothyroidism (32), atopic dermatitis (33) and self-reported allergy (34). ZBTB10 is thought to regulate specificity proteins Sp1, Sp3 and Sp4 (35,36); in cell culture studies, it is suppressed by ROSmicroRNA27a, thereby enhancing estrogen receptor α expression and mediating estrogen effects (36). Potential immunoregulation could either be through Sp1 (critical for interleukin [IL]-10 and CD40 responses) (37,38) or indirectly via estrogen effects on autoimmunity (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al confirmed that antisense microRNA-27a and overexpression of ZBTB10 blocked estrogen-induced transactivation in breast cancer (15). These studies suggest that microRNA-27a: ZBTB10-specificity protein pathway mediates hormone-induced bio-function.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, many features of previously mentioned syndromes (i.e., chromosomal instability, cancer) can be explained by problems associated to chromosome segrega- tion and mitosis, which might result from improper p44 downregulation. In that regard, the overexpression of miR-27a in several cancer types has been proposed to promote oncogenic features, supporting that improper transcriptional shutdown/ inefficient DNA repair might lead to improper resolution of mitosis and cancer (32,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 95%